2017
DOI: 10.1088/2058-6272/aa8765
|View full text |Cite
|
Sign up to set email alerts
|

Solitary kinetic Alfvén waves in a dense electron–positron–ion plasma with degenerate electrons and positrons

Abstract: Through the use of a reductive perturbation technique, solitary kinetic Alfvén waves (KAWs) are investigated in a low but finite b (particle-to-magnetic pressure ratio) dense electron-positron-ion plasma where electrons and positrons are degenerate. The degenerate plasma model considered here permits the existence of sub-Alfvénic compressive solitary KAWs. The influence of r (equilibrium positron-to-ion density ratio), s F (electron-to-positron Fermi temperature ratio), b and obliqueness parameter l z on vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…u l 1 z 0  + / (in dimensionless form) to be smaller than one suggesting the existence of solitons at sub-Alfvénic speed [40]. It is to be noted that the existence of sub-Alfvénic compressive solitary KAWs in our relativistic degenerate e-p-i plasma system is in agreement with those reported recently in degenerate e-p-i [35] as well as in e-i [41] plasmas but differs from reference [11] where supersonic, subsonic, and super-and sub-Alfvénic solitary waves were predicted in degenerate quantum e-i plasma under different relativistic regimes. This result is also similar to that reported in nondegenerate e-p-i plasmas [42][43][44], but is different from reference [45] where compressive solitons both at sub-and super-Alfvénic regime, were reported.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…u l 1 z 0  + / (in dimensionless form) to be smaller than one suggesting the existence of solitons at sub-Alfvénic speed [40]. It is to be noted that the existence of sub-Alfvénic compressive solitary KAWs in our relativistic degenerate e-p-i plasma system is in agreement with those reported recently in degenerate e-p-i [35] as well as in e-i [41] plasmas but differs from reference [11] where supersonic, subsonic, and super-and sub-Alfvénic solitary waves were predicted in degenerate quantum e-i plasma under different relativistic regimes. This result is also similar to that reported in nondegenerate e-p-i plasmas [42][43][44], but is different from reference [45] where compressive solitons both at sub-and super-Alfvénic regime, were reported.…”
Section: Resultssupporting
confidence: 90%
“…We seek steady state soliton solution of the KdV equation (35). So, we introduce moving co-ordinate u , 0…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that such low-frequency (compared to the ion-cyclotron frequency) KAWs can evolve into intermediate shocks due to the anomalous dissipation, Alfvénic solitons and magnetic kink that are relevant in the solar wind for acceleration of charged particles [8]. Furthermore, the dispersion properties of KAWs and the formation of localized structures, as well as the onset of turbulence have been investigated owing to their applications in space and astrophysical plasmas [2,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%